Smart city development in Hong Kong. Issue 1 (17th June 2019) - ,
Abstract : The Government of the Hong Kong Special Administrative Region published its first Smart City Blueprint for Hong Kong in December 2017 with the vision to embrace innovation and technology to build a world‐famed Smart Hong Kong characterised by a strong economy and high quality of living. The blueprint maps out development plans covering six major areas, namely 'smart mobility', 'smart living', 'smart environment', 'smart people', 'smart government' and 'smart economy', in the following five years (up to 2022) and beyond. With over 70 initiatives set out in the blueprint, Hong Kong aims to be better equipped to address urban challenges, enhance the effectiveness of city management and improve people's quality of living as well as Hong Kong's sustainability, efficiency, and safety.